REKONTEKSTUALISASI PENJATUHAN TALAK TIGA DALAM BINGKAI NEGARA INDONESIA - Syaiful Annas (Al-Usroh : Jurnal Hukum Keluarga Islam, 2023)
This study discusses the law of three divorces in one word or one assembly which often occurs in Muslim societies. The basis used as a reference is the hadith of the Prophet SAW and Fiqh. As a rule of law country, Indonesia has provided rules for the implementation of divorce as stipulated in Law No. 1 of 1974 concerning Marriage, Law No. 7 of 1989 concerning the Religious Courts, and the Compilation of Islamic Law. The substance is that divorce can only be carried out before a court hearing. However, there are still many practices that occur in society imposing triple talaq on a wife in one word or one assembly. This research is library research with a qualitative approach. The results of this study, that the imposition of divorce with one word or in one assembly needs to be reconstructed in understanding hadith and Fiqh as a form of ijtihad with various approaches within the framework of a rule of law that realizes the goals of the law itself.